Anxiety among otolaryngology residents during the Coronavirus Disease of 2019 pandemic in Saudi Arabia: A descriptive cross-sectional study - Hessah Saad Alsayahi; Abdulaziz Yousef Alturki; Nouf Mohammed Almansour; Zuhour Abdullah Alqahtani; Hatim Ibrahim Alassaf; Arwa Mohammad Alabdulsalam; Aseel Abdulkarim Alfahhad; Roba Mohsin Altameem; Fahad Z Alotaibi (Wolters Kluwer Medknow Publications, 2021)
Background: Otolaryngologists are among the health professionals most commonly working on the front lines against coronavirus disease of 2019 (COVID-19). They are at high risk of exposure, as well as physical and psychological stress. Nevertheless, the psychological influence of working during the pandemic still needs to be explored. Objective: This study aims to assess the anxiety symptoms among otolaryngology residents in Saudi Arabia during the novel coronavirus (COVID-19) pandemic. Materials and Methods: A cross-sectional qualitative study was carried out via a survey sent to otolaryngology residents in Saudi Arabia. The questionnaire collected demographic data and included questions using the 7-item Generalized Anxiety Disorder (GAD-7) scale to evaluate the residents' anxiety toward working during the pandemic. Data analysis was conducted using R v 3.6.2. Results: Ninety-three otolaryngology residents completed the online questionnaire with a response rate of 42.5%. Of them, 30.1% had been in contact with confirmed COVID-19 patients. More than two-thirds of the respondents (68.8%) suffered from anxiety based on the GAD-7 scale; in the results, 45.2% had mild anxiety, 12.9% had moderate anxiety, and 10.8% had severe anxiety. Almost 24% of the respondents suffered from anxiety with a score of 10 or greater on the GAD-7 used as a cutoff point. Anxiety was more prevalent in married residents compared with single ones (18.9% vs. 5.45%, P = 0.002). In addition, it was prevalent in 40% of smokers compared with 5.13% of nonsmokers (P = 0.001). Conclusion: Anxiety levels among otolaryngology residents were high during the COVID-19 pandemic.